(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
The purpose of this paper is to define the concept of monetary policy, its objectives and theories, define the concept of economic equilibrium, and analysis of the role of monetary policy and economic balance in Iraq. The researcher relied on the descriptive and quantitative approach. The time field from (2010) to (2018) , and the spatial field was Iraqi economy.One of the most important results reached by the researcher is that: Monetary policy set by the Central Bank to control the money supply to avoid inflation rates and achieve economic and monetary stability in the national economy, economic equilibrium is achieved when aggregate demand and aggregate supply are equal, and in times of inflation, the Central Bank leads to a reduction in the money supply and an increase in the price to reduce the general level of prices and to avoid inflation rates in order to maintain the purchasing power of interest for money. One of the most important recommendations recommended by the researchers is that: supporting legal independence by actually applying the texts of legislation in reality to ensure the positive impact of the independence of the Central Bank on the ultimate objectives of monetary policy, and Striving to address stagnation and depression in the Iraqi economy through monetary policy tools to support the Iraqi economy.